Record of mammals (mammalia: didelphimorphia, artiodactyla, carnivora, cingulata, lagomorpha, pilosa and rodentia) in private natural reserves in Guatemala - Escobar-Anleu, Bárbara Isabela; Fuentes-Montejo, César Estuardo; Ariano-Sánchez, Daniel (Instituto de Ecología, A.C., 2017)
We documented 25 species of mammals in private natural reserves in Guatemala, mainly through camera traps, from May 2010 to October 2015. Species belong to the orders Carnivora (13), Rodentia (3), Didelphimorphia (3), Artiodactyla (2), Lagomorpha (2), Cingulata (1) and Pilosa (1). Of the species reported, 21 were found in locations not documented in the literature or on databases available online, which reflects the importance of doing research in private natural reserves.